Role of serum melatonin and oxidative stress in childhood atopic dermatitis: A prospective study - Shanthy Devadasan; Rashmi Sarkar; Krishna Deb Barman; Smita Kaushik (Wolters Kluwer Medknow Publications, 2020)
Background: Many factors have been implicated in the pathogenesis of atopic dermatitis (AD) and recently the role of oxidative damage has been postulated. Objectives: To study the levels of oxidants and antioxidants including melatonin in the blood of children with AD and their association with the severity of AD. Methods: Thirty patients with atopic dermatitis, aged 6 months to 12 years, and equal number of age and sex-matched controls were included. Clinical characteristics and baseline severity assessment using SCORAD (scoring atopic dermatitis) severity index were noted. Blood superoxide dismutase, blood glutathione peroxidase, serum malondialdehyde, and serum melatonin levels were measured in cases and controls and results were compared. Results: The serum levels of malondialdehyde and melatonin were significantly higher among the cases compared to controls. The blood levels of superoxide dismutase and glutathione peroxidase were higher in cases but the difference with controls was not statistically significant. There was no significant correlation between these markers and the severity of the disease. Conclusions: Oxidative stress was increased in cases of childhood AD compared to the control group in this study. No correlation between oxidative stress and the severity of the disease was found. Larger studies are warranted.